FAKTOR-FAKTOR YANG MEMENGARUHI CONCEPTION RATE SAPI PERAH PADA PETERNAKAN RAKYAT DI PROVINSI LAMPUNG - Fadhil, Muhammad; Hartono, Madi; Suharyati, Sri (Jurnal Riset dan Inovasi Peternakan, 2017)
The purpose of this research are to know value conception rate and the factors and magnitude factors which disturb conception rate dairy cattle at public farm onLampung Province.  This Research was held on June until July 2016 by using dairy cattle that had been inseminated of 79 dairy cattle,14 farmers, and 4 inseminators inLampung Province.  Analysis data used in the research was regression analysis.  The result showed that Conception Rate of dairy cattle at Lampung Province is 44,30%.  Factors that affect the conception rate are  reason raising as a sideline that positively associated with factor value 12,087, herdsman knowledge that negatively associated with factor value10,630, amount offoragefactorthat positively associated with factor value 0,069, frequency of concentratethat positively associated with factor value 1,069, number ofconcentratethat negatively associated with  factor value0,390, the system of provision of  water that positively associated with factor value 3,531. Keywords :  Conception Rate, Dairy Cattle, Factors and Value, Public Farm